Sexual dimorphism in acute myocardial infarction-induced acute kidney injury: cardiorenal deteriorating effects of ovariectomy in premenopausal female mice. Issue 1 (5th January 2023) - Habeichi, Nada J.; Ghali, Rana; Mroueh, Ali; Kaplan, Abdullah; Tannous, Cynthia; Jurjus, Abdo; Amin, Ghadir; Mericskay, Mathias; Booz, George W.; El-Yazbi, Ahmed; Zouein, Fouad A.
Abstract: Acute kidney injury (AKI) is a common complication of cardiovascular diseases (CVDs) in both males and females, increasing mortality rate substantially. Premenopausal females appear to be more protected, suggesting a potential protective role of female sex hormones. Here, we tested the hypothesis that ovariectomy (OVX) eliminates the beneficial effect of female sex on renal protection following acute myocardial infarction (MI). Seven days post-MI, both sexes exhibited worsened kidney function and a substantial decrease in total kidney NAD levels. Unlike MI female mice, MI males showed exacerbated morphological alterations with increased proinflammatory, proapoptotic, and profibrotic biomarkers. The expression of NAD + biosynthetic enzymes NAMPT and NMRK-1 was increased in MI females only, while males showed a substantial increase in NAD + consuming enzyme PARP-1. OVX did not eliminate the female-sex protection of glomerular morphology but was associated with swelling of proximal convoluted tubules with MI as in males. With OVX, MI females had enhanced proinflammatory cytokine release, and a further decrease in creatinine clearance and urine output was observed. Our findings suggest that MI induced AKI in both sexes with pre-menopausal female mice being more protected. Ovariectomy worsens aspects of AKI in females after MI, which may portend increased risk for development of chronic kidney disease.